Kebinekaan Kebinekaan dan Mini Talkshow di Metro TV - Rona Marina Nisaasari (Communicology: Jurnal Ilmu Komunikasi, 2020)
Abstract This article discussed about diversity and the production management of an annual event program in order to welcome the Christmas and New Year 2018 – 2019. The program called the Christmas and New Year Pre Event program 2018 – 2019 with the theme of "Sharing Love in Diversity". This program presented by Metro TV as the pioneer of news background television in Indonesia. The purpose of this program is to provide education and perspectives from several figures representing millennials until the old one about diversity or multiculturalism and also the meaning of tolerance in Indonesia with a mini talk-show setting which had a relaxed image but weighted material. The creation of a good production management is one of the benchmarks to decide the success of an event program. At this stage the research used four main functions of production managements: (1) the planning function. (2) The organizing function in the preproduction process. (3) The directing function which influence the production process. (4) The supervisory function in the post production process based on the field observations. The production process used the interview by appointment method; that was an interview adjusting to the interviewees’ time and location. This program presented to be a conciliatory event when Indonesia was in grieve in the turning year between 2018 and 2019. Based on the research, it shows that the production management program of Christmas and New Year Pra Event 2018 - 2019 only implemented some of the standard of operations (SOP) whilst the rest was not conducted such as rehearsal. However, the processes could run very well and relate with the diversity theme. The management also implemented the four functions of production management in every step of the project. The main team which consisted of four people in this program always did sudden evaluation and fixed the weaknesses as soon as possible. The team consequently experienced some obstacles. However, the team could achieve the success in the end. Keywords : Metro TV, Mini Talk-show, Sharing Love in Diversity Abstrak Artikel ini membahas mengenai kebinekaan dan manajemen produksi sebuah program event yang terjadi setahun sekali dalam rangka menyambut peringatan Natal dan Tahun Baru 2018 – 2019 yang dipersembahkan oleh Metro TV dengan background televisi berita pertama di Indonesia yakni program Pra Event Natal dan Tahun Baru 2018 – 2019 di Metro TV dengan tema “Berbagi Kasih dalam Kebinekaan”. Tujuan dari program ini adalah memberikan edukasi dan pandangan dari beberapa tokoh yang mewakili kaum millennial hingga tua tentang keberagaman atau multikulturalisme beserta makna toleransi yang ada di Indonesia dengan format mini talkshow yang memiliki kesan santai tetapi dengan materi yang berbobot. Terciptanya manajemen produksi yang baik adalah salah satu tolak ukur berhasilnya sebuah program acara, pada tahapan ini penelitian menggunakan empat fungsi utama manajemen produksi yaitu fungsi perencanaan dan fungsi pengorganisasian pada proses pra produksi, fungsi pengarahan dan memberikan pengaruh pada proses produksi serta fungsi pengawasan pada proses pasca produksi berdasarkan observasi dilapangan. Pada proses produksinya menggunakan metode interview by appointment yaitu wawancara dengan menyesuaikan narasumber berdasarkan lokasi maupun waktunya. Program ini hadir sebagai pendamai dengan melihat keadaan Indonesia yang sedang berduka pada penghujung pergantian tahun 2018 ke 2019. Berdasarkan penelitian yang telah dilakukan menunjukkan bahwa manajemen produksi program Pra Event Natal dan Tahun Baru 2018 – 2019 menggunakan standar SOP yang tidak semuanya dilakukan, seperi rehearsal tetapi prosesnya berjalan lancar sesuai dengan tema yaitu tentang keberagaman dan menerapkan keempat fungsi manajemen produksi pada setiap prosesnya. Tim inti pada program ini juga selalu melakukan evaluasi dadakan dan segera memperbaiki kekurangan meskipun hanya terdiri dari empat orang yang beberapa kali mengalami kewalahan, namun dibalik itu semua mampu mencapai keberhasilan. Kata Kunci : Metro TV, Mini Talkshow, Berbagi Kasih dalam Kebinekaan